Jewish terrorist activities and the British government in Palestine, 1939-1947 - Hoffman, BR (1986)
﻿ From 1939 to 1947 two Jewish terrorist organizations, the Irgun Zvai Leumi and the Lohamei Herut Israel (known to Jews by its Hebrew acronym, Lehi, and to the British as "The Stern Gang") challenged Britain's rule over Palestine. Those eight years began with the publication of the White Paper in May 1939 and ended in September 1947 with the decision taken by the British Government to surrender its League of Nations Mandate and withdraw from Palestine. This thesis examines the influence that Jewish terrorist activities had on Britain's policy for Palestine and seeks to ascertain the role played by terrorism in that decision. Through an examination of British policy and the strategies employed by the British Army to defeat the terrorists, this study demonstrates why the British failed to reach either a military or a political settlement in Palestine. This failure can.be attributed both to the irreconcilable nature of Arab and Jewish claims to the country and the lack of a clear and consistent policy for Palestine on Britain's part. The situation was further aggravated by the weaknesses of the Palestine Police Force, the futile efforts of the Palestine Government to obtain the cooperation of the Jewish public against the terrorists and the debilitating effect of Jewish terrorist activities on the morale of the British soldier in Palestine. The search for a solution to the Palestine problem after World War II took place amid increasing terrorist violence in the country. As British authority in Palestine deteriorated, Britain's will to remain there dissolved. This thesis concludes that no single factor itself can be considered responsible for the decision to surrender the mandate and leave Palestine. At the same time, however, Jewish terrorist activities played an important--and even a decisive--role in the events that led to the termination of British rule over Palestine and the establishment of the State of Israel.